A Phase 2, Placebo‐Controlled Study of the Opioid Receptor Antagonist LY2196044 for the Treatment of Alcohol Dependence. (6th September 2013) - Wong, Conrad J.; Witcher, Jennifer; Mallinckrodt, Craig; Dean, Robert A.; Anton, Raymond F.; Chen, Yunfei; Fijal, Bonnie A.; Ouyang, Haojun; Dharia, Sweta; Sundseth, Scott S.; Schuh, Kory J.; Kinon, Bruce J.
<x xml:space="preserve">Abstract</x> Background Endogenous opioid‐mediated reward pathways may play a role in the development and maintenance of alcohol dependence. This study tested whether LY2196044, an opioid receptor antagonist, in combination with medical management would reduce drinking in alcohol‐dependent patients. Methods This was a multicenter, outpatient, randomized, double‐blind, parallel, and placebo‐controlled trial with a 16‐week treatment period. Patients (N = 375) were alcohol‐dependent, treatment‐seeking adults. Patients were randomly assigned to once‐daily LY2196044 (final doses of 125 or 250 mg/d) or placebo. DNA samples were collected at baseline. At each visit, patients underwent safety assessments, laboratory testing, efficacy measures, and medical management. Blood samples were also obtained for pharmacokinetic testing. The primary measure was the change from baseline in the percent heavy drinking days (HDD). Secondary efficacy measures were percent days abstinent per month and number of drinks per day. Results The treatment difference in change from baseline in % HDD between LY2196044 and placebo was not statistically significant (−43.02 vs. −38.72%, respectively; p = 0.12). There was a trend toward greater change from baseline in the percent days abstinent per month for the LY2196044 group compared with the placebo group (33.49 vs. 28.12%, respectively; p = 0.051). The decrease from baseline for mean number of drinks per day was statistically significantly greater in the LY2196044 group compared with the placebo group (−5.37 vs. −4.66 drinks per day, respectively; p = 0.013). LY2196044‐treated patients who were dopamine receptor type 4–variable number tandem repeat L carriers had greater reductions in % HDD (p = 0.0565), increased percent days abstinent (p = 0.0496), and reduced drinks per day (p = 0.0069) than placebo‐treated L carriers. The safety profile for LY2196044 appeared similar to that of other opioid antagonists. Conclusions The results from this proof‐of‐concept clinical trial warrant further evaluation of LY2196044 for the treatment of alcohol dependence.